Population awareness of cardiovascular disease and its risk factors in Buea, Cameroon - Leopold Ndemnge Aminde; Noah Takah; Calypse Ngwasiri; Jean Jacques Noubiap; Maxime Tindong; Anastase Dzudie; J. Lennert Veerman (BMC, 2017)
Abstract Background Adequate awareness of cardiovascular diseases (CVD) and their risk factors may help reduce the population's exposure to modifiable risk factors and thereby contribute to prevention and control strategies. There is limited data on knowledge among the general population in sub-Saharan Africa regarding CVD and risk factors. We aimed to assess the population awareness (and associated factors) of CVD types and risk factors in Buea, Cameroon. Methods This was a community-based cross-sectional study conducted in 2016 among randomly selected adults (>18 years). Data on socio-demographic characteristics, knowledge about CVD types, their risk factors and warning signs for CVD events (stroke and heart attack) were acquired using a self-administered questionnaire. Logistic regression analysis was used to investigate factors associated with moderate-to-good knowledge. Results Of the 1162 participants (61.7% women, mean age 32 years), 52.5% had overall poor knowledge (mean score 12.1 on total of 25) on CVD with only about a quarter correctly identifying types of CVD. Overall, 36, 63 and 45% were unaware of CVD risk factors, warning signs of heart attack and stroke respectively. In multivariable analysis; high level of education (aOR = 2.26 (1.69-3.02), p < 0.0001), high monthly income (aOR = 1.64 (1.07-2.51), p = 0.023), having a family history of CVD (aOR = 1.59 (1.21-2.09), p = 0.001) and being a former smoker (aOR = 1.11 (1.02-1.95), p = 0.043) were associated with moderate-to-good knowledge. Conclusions There exists a significant gap in population awareness about CVDs in Cameroon and this is similar to previous reports. Cost-effective community health education interventions taking into account socioeconomic status may be beneficial in this setting.